Correlation between vitamin D levels and bone metabolism in children with cow's milk allergy. Issue 1 (January 2022) - Che, Di; Yu, Li; Guo, Yong; Ke, Hai-jin; Liu, Cui; Wu, Jie-Ling
Objective: Research is limited regarding biochemical markers of bone metabolism among children with cow's milk protein allergy (CMPA). We aimed to determine differences in vitamin D and bone metabolism markers between infants with CMPA and healthy infants and explore relationships between these in a cross-sectional study. Methods: In total, we included 41 children diagnosed with CMPA and under systematic medical and nutritional care at our center, and 50 healthy children as a control group. We reviewed demographic and clinical characteristics and measured serum biomarkers. Results: We found that serum 25-hydroxyvitamin D (25(OH)D) levels among infants in the CMPA group were significantly lower than those in the control group, and levels of bone-specific alkaline phosphatase (BALP), serum phosphorus, and serum calcitonin were reduced. Pearson correlation analysis showed that serum 25(OH)D concentrations in the CMPA group were negatively correlated with parathyroid hormone but not significantly correlated with calcitonin and BALP. Logistic regression showed that CMPA was a risk factor for vitamin D deficiency. Conclusions: Our study indicated that CMPA was associated with disturbances in bone metabolism. Levels of vitamin D in children with CMPA were lower than those in healthy children. CMPA was a risk factor for vitamin D deficiency.